Communication between Health Professionals and Community Residents in Fukushima: A Focus on the Feedback Loop. Issue 10 (23rd August 2020) - Yumiya, Yui; Goto, Aya; Murakami, Michio; Ohira, Tetsuya; Rudd, Rima E.
ABSTRACT: Interactive communication and the ability to consider feedback are critical for linking health professionals and the community. Goto and colleagues developed and conducted health literacy training workshops for public health nurses after the 2011 nuclear accident in Fukushima to improve their communication skills. The present study aimed to examine the association between past workshop attendance and nurses' attitudes toward feedback from community residents. We conducted a questionnaire survey with 723 public health nurses in Fukushima and analyzed differences in feedback acceptance, work environment, basic characteristics, and health literacy levels between health literacy workshop attendees and non-attendees. Among 582 respondents, 19.4% were past attendees and showed a higher likelihood of accepting feedback from community residents (amount: adjusted odds ratio [aOR] = 1.87, 95% confidence interval [CI]: 1.21–2.88; specificity: aOR = 1.69, 95%CI: 1.09–2.61; satisfaction: aOR = 2.34, 95%CI: 1.50–3.65) than did non-attendees after adjusting for other variables. Furthermore, work engagement was associated with positive feedback acceptance (amount: aOR = 1.43, 95%CI: 1.03–1.98; specificity: aOR = 1.57, 95%CI: 1.12–2.20; satisfaction: aOR = 1.97, 95%CI: 1.38–2.81). We note the importance of creating a better work environment as well as a training system at the organizational level that encourages public health nurses to learn about health literacy and to improve their communication skills. This could improve professional/community relationships, increase the accessibility of health information for the public, and ultimately improve community health.